The Standardization of Uveitis Nomenclature (SUN) Project - Trusko, B.; Thorne, J.; Jabs, D.; Belfort, R.; Dick, A.; Gangaputra, S.; Nussenblatt, R.; Okada, A.; Rosenbaum, J.; for The Standardization of Uveitis Nomenclature (SUN) Project (Methods of Information in Medicine, 2013)
Background: Given the recent increased focus on evidence-based medicine, it is critical that diseases and syndromes have accurate and complete descriptions, including standardized and widely accepted terminologies. Standardizing these descriptions and terminologies is necessary to develop tools such as computerized data entry forms and classification criteria. This need is especially true for diseases that are relatively uncommon, such as uveitis.Objectives: To develop a standardized and internationally accepted terminology for the field of uveitis.Methods: The Standardization of Uveitis Nomenclature (SUN) Working Group (WG) is an international group of 79 uveitis experts from 18 countries and 62 clinical centers. Initial terminology was developed utilizing a “modified” green field approach, which was enhanced through web-based surveys and teleconferences via a “modified” Delphi technique. Terms were mapped provisionally into ontologic dimensions for each syndrome. The Working Group then met and utilized nominal group techniques as a formalized method of finalizing the mappings.Results: Mapping of terms into dimensions to describe 28 major uveitic diseases was confirmed using nominal group techniques (achieving super-majority consensus) for each of the diseases at a meeting of the entire WG.Conclusions: The SUN WG utilized an informatics-based approach to develop a stand ardized and internationally accepted terminology for the uveitides.
Keywords: Classification criteria; uveitis; Delphi technique; nominal group techniques; standardized terminology